Web development for auto-assessment platform - Heng, Esmond Fuwei (Nanyang Technological University, 2022)
The worldwide pandemic has interrupted students around the globe. During this period, Examinations have been halted in Singapore large-scale gathering was prohibited due to the safe distancing measure. This propels educational institutions to shift examinations to online and there is a rising demand for an online platform that could meet their needs. Firstly, various existing online platforms are examined to investigate how assessment in an internet learning environment could be held to ensure a more efficient and conducive examination process for both students and lecturers in ensuring that the application is secured and well maintained to prevent any leakage or change of data from unknown sources. Next, several functionalities are developed according to the needs of each group of users. For administrators and lecturers, a user-friendly graphical overview of student performance is provided for them to better understand student performance. For the technical support team, a series of meaningful analytical logs that record users’ usage of the application would be sent for them to monitor the technical records and promptly identify any misuse of the application such that quick actions could be taken to rectify any issues. For example, the system could identify unauthorized users and ban the corresponding IP address accordingly.